Modelamiento del escurrimiento por el software Hec-Hms para predecir el comportamiento hídrico de la subcuenca del río Carrizal - Santos Rueda, Martha Daniela (2017)
The objective of this research was to validate the modeling of the rainfall-drainage process adapted to the Carrizal River subbasin, located in the eastern end of the Province of Manabí, whose purpose was to analyze and simulate the hydrological behavior of the precipitations and the corresponding flow through The calibration of the hydrological mathematical model HEC-HMS (Hydrologic Engineering Center's Hydrologic Modeling System) and the application of the HEC-RAS extension; Where the HEC-HMS software allowed to represent with sufficient precision the water behavior of the selected years 2011-2015, obtaining as a result that in 2012 was where the highest precipitation that caused floods in the province of Manabí occurred. For the study of these mathematical models of infiltration, runoff, and floods, rainfall and flow data from the ESPAM monitoring station were analyzed, facilitating the identification of flood risk areas and, therefore, approval of the estimation models of the rain - drainage process in the Carrizal river sub - basin. As a final conclusion, the HEC-HMS program helped to model the loss of soil infiltration in the highest rainfall months in the area, with meteorological data entered into the program, which shows the hydrological behavior of the river subbasin of the selected years, Determining the maximum flows and precipitations, through the results obtained was predicted using the Gumbel equation the water behavior of the next years for the subbasin of the Carrizal river.